DRY EYE DISEASE AND RISKS OF URBAN AIR POLLUTION – LITERATURE REVIEW - Natasha Trpevska Shekerinov; Andrijana Petrushevska; Emilija Gjoshevska Dashtevska; Toni Shekerinov; Jana Nivichka Kjaeva (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2022)
Air pollution has a major impact on health, and it particularly affects the mucous membranes of the respiratory tract and the eyes. The ocular effects of chronic, long-term exposure to high levels of air pollution are still unclear. The increase in air pollution levels can be associated with an increase in the instability of the tear film. The aim of this paper is to evaluate and discuss the available data about chronic eye diseases in regions with high air pollution. Furthermore, the review also offers a certain understanding of the link between chronic dry eye disease (DED) and air pollution. Materials and methods: Specific keywords (dry eye, air pollution, and urban) were used to search the medical databases of PubMed and Medline. This research technique led to obtaining 103 papers, dating from 1995 to 2021. Out of those, 15 were used as the basis of this paper. Results: The pathophysiological mechanisms of oxidative stress and ocular surface inflammation involve the selective binding of environmental agents to ocular surface membrane receptors, leading to the activation of proinflammatory signaling pathways with changes in the extracellular stromal matrix and consequent occurrence of inflammation of the ocular surface with epithelial defects. Conclusions: Dry eye disease, pollution, and eye allergy overlap, but their presentations can be different. Future advancements in monitoring technology and the development of modern, noninvasive diagnostic methods will help prove the link between air pollutants and DED. The points should be aimed at preventing the global risks of antigenic stimulation of „urban ey
Keywords: dry eye; air pollution; eye allergy